The Making of Antiquity: Japanese Experience in the Seventeenth and Eighteenth Centuries - Hiroshi Watanabe; Sayaka Oki; Atsuko Tamada (Diciottesimo Secolo)
In 18th century Japan, a nationalistic perception of antiquity evolved in direct opposition to the ideal of Confucian antiquity. While Confucianism, which idealized Chinese antiquity as a golden age of virtuous rule, appealed to the warrior class with its emphasis on universal principles and reason, a counter-movement emerged in the form of kokugaku (national learning). The movement reinterpreted ancient texts such as the Kojiki and The Tale of Genji as expressions of a distinctly Japanese mentality and culture, elevating the feminine aristocratic court culture of the Heian period (from the late 8th to the 12th centuries) as an ideal. Its leading figure, MOTOORI Norinaga, drew a sharp distinction between the karagokoro, the Chinese way of thinking, and the ‘Upright Heart’ of ancient Japanese people, which he saw as rooted in poetic sensibility and an emotional, aesthetic understanding of the world. The concept of antiquity formulated by the kokugaku played a crucial role in shaping Japanese identity and state ideology, particularly during the Meiji Revolution (1868-), when efforts to restore imperial rule and establish a centralised government ultimately dismantled the ancient regime associated with the warrior caste.